Desenvolvimento de tecnologia gerencial para comunicação efetiva entre a equipe de enfermagem em clínicas de hemodiálise (TGCE-HD - Fernandes, Cristina da Silva (2023)
Patients with chronic kidney disease who require hemodialysis are subject to risks related to their safety, among which it is worth highlighting failures in communication between the health team, which enhances the occurrence of adverse events. Thus, it is necessary to develop management technologies that aim to improve communication between the nursing team in hemodialysis clinics. Therefore, this research aimed to develop management technology for effective communication between the nursing team in hemodialysis clinics. This is a methodological study, carried out in four phases. During the first phase, an exploratory study was carried out, with a qualitative approach, to find out how communication occurs between the nursing team during the shift change in hemodialysis clinics in Ceará. The study scenarios were the following municipalities in Ceará: Barbalha, Cascavel, Eusébio, Russas and Sobral. Professionals from the nursing team who had an employment relationship with the respective institutions were included. Data were collected from the following triggering question: “How does the nursing team communicate in your unit of action and what information is transmitted during the shift change?”. The statements resulting from the interviews were processed in the Interface de R pourles Analyzes Multidimensionnelles de Textes et de Questionnaires (IRaMuTeQ) software and analyzed by Descending Hierarchical Classification (CHD). In the second phase, an integrative review was carried out with the objective of identifying recommendations on nursing shift changes in hemodialysis clinics. Articles that answered the research question were included, without delimitation of publication time and language. The third and fourth phases of this research were the construction and validation of the technology, based on the results of the previous phases. Content validation was carried out by 22 expert judges, who evaluated the technology for clarity, practical pertinence and theoretical relevance. Data analysis was performed using the content validity coefficient. In this research, a minimum concordance of 0.80 was adopted. Data were treated from absolute and relative frequencies, descriptive measures and the binomial test. A significance level of 5% and a confidence interval of 95% were used. In the first phase, 44 professionals participated. After analyzing the data, it was possible to identify the following classes: information transmitted during the shift change; failures in communication between the nursing team; technologies that facilitate communication between the nursing team; perceptions of professionals about communication between the nursing team. The integrative review had a sample of six articles. After analysis, four categories were identified, namely: general guidelines for shift change; patient information; nursing routines; human resources and organization of the environment. Technology was divided into general guidelines, followed by four domains on: human resources and organization of the environment; nursing routines; information about the patient and prioritization of care to be performed during the shift. In the validation, it reached a total content validity coefficient of 0.93, with an error for polarization of the judges of 0.00. The technology reached a coefficient of 0.94, 0.92 and 0.93, in the aspects: clarity, practical relevance and theoretical relevance, respectively and there was no statistical significance, from the application of the binomial test for each item of the technology. Therefore, the product of this research consisted of a tool called Management Technology for Effective Communication between the Nursing Team in Hemodialysis Clinics, which is validated and can be incorporated into the work routine in hemodialysis services.